Intralesional steroid treatment for the intermediate stage of retronychia: A pilot study. Issue 6 (14th September 2020) - Alessandrini, Aurora; Sechi, Andrea; Merli, Yuri; Bruni, Francesca; Piraccini, Bianca Maria; Starace, Michela
Abstract: Retronychia describes the proximal ingrowing of the nail plate. In the early stage, topical steroids are the gold standard therapy, while in the late stage surgical treatment is mandatory. We identified an intermediate severity stage of retronychia, where the topical treatment alone is ineffective and surgery is avoidable. Intralesional steroids turn the best treatment in these patients. A pilot study consisting of a 3‐month treatment period and 9‐month follow‐up time was designed to evaluate the treatment outcome to intralesional steroid injections in patients affected by the intermediate‐stage of toenail retronychia. The complete recovery of retronychia‐associated nail abnormalities was observed in 27/28 recruited patients at the end of the treatment phase. Paronychia, nail plate discoloration, proximal nail fold (PNF) elevation, and discharge were reduced ( P < .01) after one steroid administration, while nail regrowth became significant after two sessions. No significant difference in terms of clinical outcome was found, while pain VAS score and intra‐operative pain evaluated with Wong‐Baker faces scale were higher in the female group ( P < .01). Limitation Lack of control group of patients. Despite its temporary effect, the intralesional triamcinolone injection is an effective, cheap, and safe treatment especially for the intermediate stage of retronychia.